LJUBOMIR SIMOVIĆ'S HASANAGINICA IN THE CONTEXT OF THE AUTHOR'S OPUS (Philological Studies, 2019)
The play Hasanaginica by Ljubomir Simović transposes the basic constitutive elements of the folk ballad, placing them in a new framework with discursive practices that are determined by the tradition to which they are associated, as well as according to their own modernity, which is attempted by re-writing tradition. The most discussed methods are present in the language of the drama action. The holders of dramatic events thus gain different positions in invoking, or destroying the mythical structure, which is a pretext of drama. In this paper, the specificity of the authorial approach to the parent text is analyzed by breaking up the elementary language elements from which the basic text is removed. Particular attention is paid to the synchronized use of various functional styles, which in the drama acquires a narrower and wider meaning - both in terms of terms and content.
Keywords: Hasanaginica, Ljubomir Simović, poetry, drama, resemantization of tradition